Analysis of Declared Preferences on Sustainable Mobility in the city of Santa Fe (AACINI - International Journal of Industrial Engineering, 2023)
In recent decades, changes in lifestyle and urban and territorial models have been generating increasing difficulties in mobility. These include: traffic congestion, environmental and social impacts that affect people's quality of life. From this concern arises the concept of sustainable mobility that promotes a balance between economic, social and environmental benefits. To achieve progress in this sense, public policies are needed that promote public transport, cycling or walking, providing benefits to the environment and the quality of life of the population. In order to recognize the trends and expectations of the population of the city of Santa Fe on the problem, it is necessary to use discrete choice models based on a sample of individuals from declared preference surveys, considering the existing modes of transportation and the potentials.The work is included in the PID-TVTCBFE0008072TC: "Design of strategies for the promotion of sustainable mobility in urban agglomerates", seeking to present the analysis of the declared preference surveys carried out in June 2022 to a representative sample of people from the city of Santa Fe where they were consulted about how they would act in different hypothetical situations that were presented to them in order to establish the potential for success of different sustainable mobility policies.
Keywords: Urban movility; Preferencies; Sustainability; Surverys